2019
DOI: 10.32722/epi.v16i1.1423
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Hypnoteaching Untuk Meningkatkan Kemampuan Self-Regulated Learning Mahasiswa Papua Dalam Mata Kuliah Desain Pembelajaran

Abstract: __________________________________________________________________________ AbstractThe low ability of Self-Regulated Learning students who mostly come from the remote area in Papua, motivates researchers to conduct research by applying Hypnoteaching in the learning process. One of the reasons for the low ability of Self-Regulated Learning students is the habit of those who have not been able to regulate and direct themselves in learning. Hypnoteaching, also called giving positive suggestions, is expected to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
1
1
0
2
Order By: Relevance
“…This research also found that PAI course activities trigger students' ability to control themselves in the form of learning effi ciency. The results of this research are in accordance with Edistria's research which reveals that students' self-control skills are one of the indicators of self-learning (Edistria, Rahman, & Abdillah, 2019). The conditions of online learning today require an adaptive attitude of students towards the development of information technology (IT) as the main media for online learning.…”
Section: Finding and Discussionsupporting
confidence: 85%
“…This research also found that PAI course activities trigger students' ability to control themselves in the form of learning effi ciency. The results of this research are in accordance with Edistria's research which reveals that students' self-control skills are one of the indicators of self-learning (Edistria, Rahman, & Abdillah, 2019). The conditions of online learning today require an adaptive attitude of students towards the development of information technology (IT) as the main media for online learning.…”
Section: Finding and Discussionsupporting
confidence: 85%
“…The Hypnoteaching method better improves students' problem-solving skills and concept understanding compared to the conventional teaching methods because the students are given examples of questions about algebraic form material to be discussed with the group during the learning process. The Hypnoteaching learning method also makes students more focused in the group discussion process because the group discussion stages in the Hypnoteaching method are structured that can motivate and can make learning more interesting [27].…”
Section: Resultsmentioning
confidence: 99%
“…Diindikasikan secara lebih kongkrit pada penelitian dukungan dan dukungan teman sebagai variabel yang berkontribusi terhadap self-regulated learning, artinya dukungan orangtua terhadap anak dalam belajar dan dukungan teman sebaya dalam belajar berkontribusi terhadap self-regulated learning peserta didik. Pada dasarnya self-regulated learning sebagai wujud dari perilaku belajar dipengaruhi oleh faktor lingkungan dan faktor personal [32]. Hal ini sebagai pengembangan lebih dalam pada teori kognitif sosial yang telah dilakukan [5], [32].…”
Section: Hasil Dan Pembahasanunclassified